Learning the Roles of the Hepatic Adaptive Immune System in Hepatocellular Carcinoma—Nature's Guide for Successful Cancer Immunotherapy - Heikenwälder, Mathias; Pikarsky, Eli (Seminars in Liver Disease, 2017)
The different roles of the adaptive immune system in cancer are beginning to unfold. The dramatic responses to immune check point drugs in some tumors generated an accelerated need for understanding the complex set of interactions between tumor and immune cells. In view of the major pathophysiological role of immune cells in hepatocellular carcinoma, it is not surprising that malignant hepatocytes interact extensively with adaptive immune cells, resulting in both protumor immunopathology and antitumor protective immunity. Identifying potential responders to drugs that target the adaptive immune system, monitoring their immune response to the tumor, and devising the best treatment combinations depends on understanding the complex set of interactions taking place within the tumor and in the adjacent hepatic parenchyma.
Keywords: hepatocellular carcinoma; immunotherapy; immune checkpoint; mouse models; immunosuppression; chronic inflammation